\(\int {adx} = ax + C\) |
\(\int {xdx} = {\large\frac{{{x^2}}}{2}\normalsize} + C\) |
\(\int {{x^2}dx} = {\large\frac{{{x^3}}}{3}\normalsize} + C\) |
\(\int {{x^p}dx} = {\large\frac{{{x^{p + 1}}}}{{p + 1}}\normalsize} + C\) |
\(\int {\large\frac{{dx}}{x}\normalsize} = \ln \left| x \right| + C\) |
\(\int {{e^x}dx} = {e^x} + C\) |
\(\int {{b^x}dx} = {\large\frac{{{b^x}}}{{\ln b}}\normalsize} + C\) |
\(\int {\sin xdx} = - \cos x + C\) |
\(\int {\cos xdx} = \sin x + C\) |
\(\int {\tan xdx} = - \ln \left| {\cos x} \right| + C\) |
\(\int {\cot xdx} = \ln \left| {\sin x} \right| + C\) |
\(\int {\sec xdx} = \ln \left| {\tan\left( {\large\frac{x}{2}\normalsize + \large\frac{\pi }{4}\normalsize} \right)} \right| + C\) |
\(\int {\csc xdx} = \ln \left| {\tan\large\frac{x}{2}\normalsize} \right| + C\) |
\(\int {{\sec^2}xdx} = \tan x + C\) |
\(\int {{\csc^2}xdx} = -\cot x + C\) |
\(\int {\sec x\tan xdx} = \sec x + C\) |
\(\int {\csc x\cot xdx} = -\csc x + C\) |
\(\int {\large\frac{{dx}}{{1 + {x^2}}}\normalsize} = \arctan x + C\) |
\(\int {\large\frac{{dx}}{{{a^2} + {x^2}}}\normalsize} = {\large\frac{1}{a}\normalsize}\arctan {\large\frac{x}{a}\normalsize} + C\) |
\(\int {\large\frac{{dx}}{{1 - {x^2}}}\normalsize} = {\large\frac{1}{2}\normalsize}\ln \left| {{\large\frac{{1 + x}}{{1 - x}}\normalsize}} \right| + C\) |
\(\int {\large\frac{{dx}}{{{a^2} - {x^2}}}\normalsize} = {\large\frac{1}{{2a}}\normalsize}\ln\left| {\large{\frac{{a + x}}{{a - x}}\normalsize}} \right| + C\) |
\(\int {\large\frac{{dx}}{{\sqrt {1 - {x^2}} }}\normalsize} = \arcsin x + C\) |
\(\int {\large\frac{{dx}}{{\sqrt {{a^2} - {x^2}} }}\normalsize} = \arcsin {\large\frac{x}{a}\normalsize} + C\) |
\(\int {\large\frac{{dx}}{{\sqrt {{x^2} \pm {a^2}} }}\normalsize} = \ln \left| {x + \sqrt {{x^2} \pm {a^2}} } \right| + C\) |
\(\int {\large\frac{{dx}}{{x\sqrt {{x^2} - 1} }}\normalsize} = \text{arcsec}\left| x \right| + C\) |
\(\int {\sinh xdx} = \cosh x + C\) |
\(\int {\cosh xdx} = \sinh x + C\) |
\(\int {{\text{sech}^2}xdx} = \tanh x + C\) |
\(\int {{\text{csch}^2}xdx} = -\text{coth}\,x + C\) |
\(\int {\text{sech}\,x\tanh xdx} = - \text{sech}\,x + C\) |
\(\int {\text{csch}\,x\coth xdx} = - \text{csch}\,x + C\) |
\(\int {\tanh xdx} = \ln \cosh x + C\) |